Identifikasi Struktur Tektonik Sistem Geothermal Non-Vulkanik Daerah Nyelanding dan Permis Bangka Selatan Menggunakan Metode Gravity - Afni, Githa Nurvilia; Kusmita, Tri (Jurusan Fisika, Universitas Bangka Belitung, 2021)
Non-volcanic geothermal is a heat system that is not related to volcanism such as in Nyelanding and Permis areas. In previous studies, hot springs in the Nyelanding area were spread from West to Northeast, with the constituent rocks of sandstone, dry gravel and granite. In the Permis area, the manifestation is influenced by shear faults trending Northwest to Southeast and the geothermal source is granite. Therefore, this study was conducted to determine the strenght of local tectonic structures using the gravity method. The data used in this study are the FAA (Free Air Anomaly) and topography data obtained through the TOPEX website. The gravity anomaly is obtained by performing spectral analysis using the Fourier Transform and moving average filter. 2D modeling is performed using inverse modeling with the smoothness constraint equation. The result of this research is that the Permis and Nyelanding geothermal systems are controlled by local tectonic structures in the Northwest and Southeast of the study area, in the form of fractures (possibly faults) with a Northeast – Southwest direction